2022
DOI: 10.1186/s13018-022-03225-y
|View full text |Cite
|
Sign up to set email alerts
|

Metformin alleviates osteoarthritis in mice by inhibiting chondrocyte ferroptosis and improving subchondral osteosclerosis and angiogenesis

Abstract: Background Osteoarthritis (OA) is the most common musculoskeletal disease, and it has a complex pathology and unknown pathogenesis. Chondrocyte ferroptosis is closely associated with the development of OA. As a common drug administered for the treatment of type 2 diabetes, metformin (Met) is known to inhibit the development of ferroptosis. However, its therapeutic effect in OA remains unknown. The present study aimed to explore the effects of Met on cartilage and subchondral bone in a mouse OA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 45 publications
2
11
0
Order By: Relevance
“…Besides its effects on bone formation, there are also interests in studying the effects of metformin on chondrocytes, especially in the context of osteoarthritis development. Limited reference showing that metformin is protective against development of osteoarthritis by reducing chondrocyte apoptosis and alleviating chondrocyte degeneration [27][28][29]. Consistent with the above reports, our data suggest that metformin promoted the cartilage formation in the endochondral ossification at day 14 post-fracture in T2D mice.…”
Section: Discussionsupporting
confidence: 92%
“…Besides its effects on bone formation, there are also interests in studying the effects of metformin on chondrocytes, especially in the context of osteoarthritis development. Limited reference showing that metformin is protective against development of osteoarthritis by reducing chondrocyte apoptosis and alleviating chondrocyte degeneration [27][28][29]. Consistent with the above reports, our data suggest that metformin promoted the cartilage formation in the endochondral ossification at day 14 post-fracture in T2D mice.…”
Section: Discussionsupporting
confidence: 92%
“…Cheng et al found that stigmasterol can inhibit ferroptosis induced by IL‐1βand improved cell viability through negatively regulating sterol regulatory element binding transcription factor 2 (SREBTF2) 215 . In addition, metformin has shown potential in the treatment of OA, as demonstrated by downregulating Gpx4 to inhibit chondrocyte ferroptosis, alleviate OA, and, to a certain extent, improve subchondral bone sclerosis and reduce angiogenesis in mice 216 …”
Section: Ferroptosismentioning
confidence: 99%
“…In experimental mouse models of advanced OA, metformin was found to suppress ferroptosis and pyroptosis in OA chondrocytes resulting in the reduction of disease alterations such as chondrocyte degradation, subchondral sclerosis and abnormal angiogenesis in the subchondral bone [30,31]. On another note, change in the microarchitecture of subchondral bone is a characteristic feature in patients with OA.…”
Section: The Rationale For Metformin Use In Osteoarthritismentioning
confidence: 99%